Virtual machine migration in cloud computing environments - Kumar, Raghvendra; Harkut, Dinesh G (IGI Global, 2018)
"This book provides an depth concepts of VM and live migration benefits and techniques and discusses its related research challenges in data center in cloud computing environments. It is a powerful and handy tool for administrators to maintain SLAs while performing optimization tasks and maintenance on the cloud infrastructure"